Functional bacterial amyloid increases Pseudomonas biofilm hydrophobicity and stiffness - Zeng, Guanghong; Vad, Brian S.; Dueholm, Morten S.; Christiansen, Gunna; Nilsson, Martin; Tolker-Nielsen, Tim; Nielsen, Per H.; Meyer, Rikke L.; Otzen, Daniel E. (Frontiers in Microbiology, 2015)
The success of Pseudomonas species as opportunistic pathogens derives in great part from their ability to form stable biofilms that offer protection against chemical and mechanical attack. The extracellular matrix of biofilms contains numerous biomolecules, and it has recently been discovered that in Pseudomonas one of the components includes -sheet rich amyloid fibrils (functional amyloid) produced by the fap operon. However, the role of the functional amyloid within the biofilm has not yet been investigated in detail. Here we investigate how the fap-based amyloid produced by Pseudomonas affects biofilm hydrophobicity and mechanical properties. Using atomic force microscopy imaging and force spectroscopy, we show that the amyloid renders individual cells more resistant to drying and alters their interactions with hydrophobic probes. Importantly, amyloid makes Pseudomonas more hydrophobic and increases biofilm stiffness 20-fold. Deletion of any one of the individual members of in the fap operon (except the putative chaperone FapA) abolishes this ability to increase biofilm stiffness and correlates with the loss of amyloid. We conclude that amyloid makes major contributions to biofilm mechanical robustness.